Monitoring athletes during training camps: Observations and translatable strategies from elite road cyclists and swimmers - Saw, A. E.; Halson, S. L.; Mujika, I. (Sports, 2018)
Monitoring is an essential yet unstandardized component of managing athletic preparation. The purpose of this paper is to provide insight into the typical measurements and responses observed from monitoring elite road cyclist and swimmers during training camps, and translate these observations to practical strategies for other practitioners to employ. Twenty-nine male professional cyclists, 12 male and 19 female international swimmers participated in up to three of the eight 4-19 day training camps, held early in the season or leading into major competitions, at sea-level or moderate altitude. Monitoring included body mass and composition, subjective sleep, urinary specific gravity (USG), resting heart rate (HR) and peripheral oxygen saturation (SpO2) at altitude. Sum of seven skinfolds most likely decreased in the order of 3.1 ± 3.6 mm week-to-week, accompanied by a most likely trivial decrease in body mass of 0.4 ± 0.4 kg week-to-week. At altitude, sleep quality very likely trivially improved week-to-week (0.3 ± 0.3 AU), SpO2 possibly increased week-to-week (0.6 ± 1.7%), whilst changes in resting HR were unclear (0 ± 4 bpm). Sleep duration and USG were stable. Comparing individual to group day-to-day change in monitored variables may prove effective to flag athletes potentially at risk of training maladaptation. Practitioners may replicate these methods to establish thresholds specific to their cohort and setting. This study provides further support for a multi-faceted approach to monitoring elite athletes in training camp environments.